KERJASAMA DALAM KELOMPOK TANI BUDIDAYA II DESA RASAU JAYA TIGA KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Khoirun Nikmah; Yohanes Bahari; Supriyadi Supriyadi (Universitas Tanjungpura, 2022)
This research aims to determine the forms of direct cooperation, contractualcooperation and traditional cooperation in the Budidaya II Farmers Group RasauJaya Tiga Village. The method used is descriptive qualitative. The methods of datacollection is using a observation methods, interview and documentation tools. Thetools of data collection is a observation guides, interview guides, and documentation.Testing of Data validity is an extension observation, and triangulation. The results ofthe research showed that the cooperation carried out in the Budidaya II FarmerGroup in the form of direct, contract and Traditional has been carried out. It isproved that there is a form of direct cooperation in the form of directives given by thechairman to its members, then a form of contractual cooperation in the form ofagreements that have been approved by all members of the group such as the holdingof meetings every month, setting monthly contributions and further a form oftraditional cooperation in which all members of the group work together in landclearing, seeding, care and harvesting of agricultural products.Keywords: Cooperation, Farmer, Farmer Groups